Teaching online : a practical guide - Ko, Susan Schor; Rossen, Steve (2017)
An accessible, introductory, practical guide for anyone who teaches online, this edition includes new and expanded information on: massive open online courses (MOOCs); teaching with mobile devices; open educational resources (OER); and learning analytics.
Part I: Getting started. Teaching online: an overview -- Scouting the territory: exploring your institution's resources -- Part II: Putting the course together. Course design and development -- Working with others to develop a course -- Creating an effective online syllabus -- Building an online classroom -- Student activities in the online environment -- Copyright, intellectual property, and open educational resources -- Creating courseware: selecting "Web2.0" tools and other resources -- Part III: Teaching in the online classroom. Preparing students for online learning -- Classroom management and facilitation -- Classroom management: special issues -- Teaching web-enhanced and blended classes -- Teaching and learning in a MOOC -- Taking advantage of new opportunities -- Glossary.
Previous edition: 2010.
Includes bibliographical references (pages [436]-470) and index.
Keywords: Education, Higher -- Computer-assisted instruction; World Wide Web -- Study and teaching (Higher); Internet in education; College teaching -- Aids and devices; Internet in higher education; Computer-assisted instruction; Distance education; Insegnamento universitario -- Impiego di internet -- Manuali